2015
DOI: 10.1111/anae.13346
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of perineural vs intravenous dexamethasone for foot surgery

Abstract: SummaryWe used 20 ml ropivacaine 0.75% for ankle blocks before foot surgery in 90 participants who we allocated in equal numbers to: perineural dexamethasone 8 mg and intravenous saline 0.9%; perineural saline 0.9% and intravenous dexamethasone 8 mg; or perineural and intravenous saline 0.9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
1
33
0
2
Order By: Relevance
“…16 Previous randomized double-blind studies reported equivalence of perineural and systemic routes using high systemic dexamethasone dose (>8 mg) when added to long-acting LAs. 17,18 Other previous randomized double-blind studies reported superiority of perineural route when using low systemic dexamethasone dose (<8 mg). 19,20 In this controversial topic, evidence based on well-designed studies should be considered.…”
Section: Discussionmentioning
confidence: 98%
“…16 Previous randomized double-blind studies reported equivalence of perineural and systemic routes using high systemic dexamethasone dose (>8 mg) when added to long-acting LAs. 17,18 Other previous randomized double-blind studies reported superiority of perineural route when using low systemic dexamethasone dose (<8 mg). 19,20 In this controversial topic, evidence based on well-designed studies should be considered.…”
Section: Discussionmentioning
confidence: 98%
“…5,6,15,19 Sensory block duration was also only reported by 5 studies, with the rest solely reporting the duration of analgesia. 5,8,[15][16][17] For these studies, perineural dexamethasone prolonged sensory block by 2.28 hours (95% CI, 0.38-4.17; P = 0.019) compared with IV dexamethasone. In sensitivity analysis where we substituted data for postoperative analgesia (where data for sensory block were missing), the direction of effect was unchanged with 3.58 hours (95% CI, 1.75-5.41; P < 0.001) longer duration with perineural dexamethasone compared to IV dexamethasone.…”
Section: Motor Block and Sensory Block Durationmentioning
confidence: 89%
“…1, PRISMA flow diagram). 5,6,8,[13][14][15][16][17][18][19][20] Notably, we excluded certain studies during our full-text review: 2 studies that compared IV/perineural clonidine and/or buprenorphine alongside dexamethasone, 21,22 one study where a continuous infusion was started prior to complete resolution of the sensory block, 23 one study where all patients received IV dexamethasone, 8 mg, 4 and finally one study where all patients received long-acting intrathecal narcotics. 24 …”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 It is not clear whether the effect of dexamethasone is primarily local or systemic. 31,32 It seems that IV dexamethasone is required in higher doses to produce the same prolongation of duration of nerve blocks. 33,34 The aim of this study was to assess the effect of dexamethasone on the duration of saphenous nerve block after major ankle surgery.…”
Section: Discussionmentioning
confidence: 99%